2023
DOI: 10.1038/s41598-023-37354-z
|View full text |Cite
|
Sign up to set email alerts
|

Biliatresone induces cholangiopathy in C57BL/6J neonates

Abstract: Exposure to plant toxins or microbiota that are able to digest common food ingredients to toxic structures might be responsible for biliary atresia (BA). An isoflavonoid, biliatresone is known to effectively alter the extrahepatic bile duct (EHBD) development in BALB/c mice. Biliatresone causes a reduction of Glutathione (GSH) levels, SOX17 downregulation and is effectively countered with N-Acetyl-L-cysteine treatment in vitro. Therefore, reversing GSH-loss appears to be a promising treatment target for a tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Biliatresone, a plant isoflavonoid-related 1,2-diaryl-2-propenone, has been implicated in BA-like syndrome outbreaks in Australian livestock [ 13 , 16 ]. It also causes bile duct destruction in zebrafish [ 13 ], mouse cholangiocyte spheroids [ 17 , 18 ], ex vivo bile duct culture [ 18 ], and mouse neonates [ 19 , 20 ]. However, evidence of the adverse effect of biliatresone on the growth of human cholangiocytes is still lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biliatresone, a plant isoflavonoid-related 1,2-diaryl-2-propenone, has been implicated in BA-like syndrome outbreaks in Australian livestock [ 13 , 16 ]. It also causes bile duct destruction in zebrafish [ 13 ], mouse cholangiocyte spheroids [ 17 , 18 ], ex vivo bile duct culture [ 18 ], and mouse neonates [ 19 , 20 ]. However, evidence of the adverse effect of biliatresone on the growth of human cholangiocytes is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The toxin biliatresone, a naturally occurring isoflavonoid-related 1,2-diaryl-2-propenone found in Dysphania glomulifera and D. littoralis , has been implicated in BA-like syndrome outbreaks in Australian livestock [ 13 , 16 ]. It also causes bile duct destruction in zebrafish [ 13 ], mouse cholangiocyte spheroids [ 17 , 18 ], ex vivo bile duct culture [ 18 ] and mouse neonates [ 19 , 20 ]. Biliatresone contains a reactive α-methylene ketone group, is highly electrophilic, and binds to reduced glutathione (GSH) [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the toxic effect of biliatresone was also confirmed in C57BL/6J mice, where the animals displayed the etiopathogenesis (jaundice, growth retardation, claycolored feces, bilirubin increase, extrahepatic obliteration) of human BA (Schmidt et al, 2023), indicating that the onset of BA induced by biliatresone is independent of the immunological background. These studies showed that biliatresone generates abnormalities observed in the hepatobiliary system in newborn mice, which are similar to human BA, reaffirming that redox stress signaling may be important in mediating the response to biliatresone-induced damage.…”
Section: Ba Bilitresone-induced Models: Micementioning
confidence: 92%